Red-Green-Blue Laser Emissions from Dye-Doped Poly(Vinyl Alcohol) Films - Yap, Seong-Shan; Siew, Wee-Ong; Tou, Teck-Yong; Ng, Seik-Weng (2002)
A microscope slide acting as a passive waveguide was coated by three separate poly(vinyl alcohol) films that were doped with Coumarin 460, Disodium Fluorescein, and Rhodamine 640 perchlorate. On collinear pumping by a nitrogen laser, these dyes furnished primary red-green-blue laser emissions that were collected and waveguided by the microscope slide but exited from both ends. Frosting the waveguide exit introduced light scattering at the glass-air interface and spatially overlaid the red-green-blue laser emissions that emerged as a uniform white-light beam. 0 2002 Optical Society of America.